Free as dead - Perrot, Romain 1973-; Bolus, Andy (Decimation sociale, 2015)
Our story concerns a man bound to death and young girl, following a path of ritualistic transfiguration to ulimately become completely free as dead. A frightening tale of evil excess, demented sorcery and lurid ritual. An orginial experimental short horror film from the twisted minds of Romain Perrot and Andy Bolus, presenting a voyage into the darkest and most psychedelic nether regions of the subconscious
Serigraphie. - Auflage 200 Exemplare
Music by Romain Perrot, sounds: Andy Bolus
Keywords: Bolus, Andy; Perrot, Romain -- 1973-; Graphzine; Film